The Relationship of Learning Motivation to Physical Fitness and the Learning Achievement of Physical Education Students - Hidayat, Zakaria Wahyu; Andrianto, Joan Rhobi (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Education has a goal related to human behaviour in various ways and sources, so the concept of learning requires an understanding of its relationship with learning as a process of gaining knowledge, experience, and making changes in the form of reactions and human nature. The purpose of this study was to see the relationship between interest in learning, physical fitness, and learning achievement. The type of research used is correlation research, which is one of the analysis techniques in statistics used to find the relationship between two quantitative variables. The results of the study for study interest and physical fitness showed significant results with a sig value of 0.03 ˂ 0.05, and the relationship between study interest and student achievement showed significant results with a sig value of 0.034 ˂ 0.05. At the level of the relationship, it is known that it is very strong between variables. The conclusion is that there is a relationship with a significant value and a very strong level of relationship between variables. The implication of the research is that when students have an interest in learning in lectures, it will have a positive impact on several aspects, including physical fitness and learning achievement.